THE PRESENCE OF REVERSE SLIP FAULT AND ITS IMPLICATION TO GEOMORPHOLOGY DEVELOPMENT AND LITOLOGY DISTRIBUTION AT CIKASO REGION, CIAMIS DISTRICT, WEST JAVA. - Haryanto, Iyan; Saputro, Anisa Ayu; Arifin, Alvin Adam; Ilmi, Nisa Nurul; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2018)
Distribution of stratigraphic sequence as the basis of various geological studies has been carried in many researches. The presence of various rock can be affected by tectonic events that have occurred before, during, and after their formation. Besides that, control of geological structure will support other research such as geomorphology, and stratigraphy. This research purpose to know what structure develop and correlation between structure and rock distribution, in Cikaso Region, Ciamis District, West Java. The method of this paper are geological mapping and studio analysis. Geological mapping carried to take out data of lithology strike dip and structure. And studio analysis to processed data with software. Geomorphology of research area are four units, that are structural hills of steep slope unit, structural hills of rather steep slope unit, structural plain of sloping slope unit, and structural plain of very sloping slope unit. There are two geology structure, are Cikaso Thrust Fault and Cigayam Sinistral Shear Fault. Based on lithostratigrapgic aspect, they are five rocks units. From old to young are Volcanic Breccia, Non Carbonate Sandstone, Clastic Limestone, Carbonate Sandstone, and Carbonate Claystone.